The using of the track-and-field exercises in the process of formation of sport style of life of children of junior education - Frolova N.A (Kharkov National Pedagogical University, 2010)
The problem of application of track-and-field exercises is lighted up for the decision of tasks of forming of sporting lifestyle junior schoolboys. The analysis of scientific literature is conducted on marked issue. Facilities of track-and-field have a wide spectrum of operating on an organism. They render assistance to the decision of health, educate and educational tasks in the process of physical education. Also form basis for mastering of maintenance of school on-line tutorial. It is well-proven that the use of facilities of track-and-field is rendered by an assistance initial sporting preparation of children in the conditions of general school.